Mechanism of action of toxic halogenated aromatics. - Vickers, A E (1985)
2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) and related halogenated aromatic hydrocarbons are a highly toxic class of environmental contaminants, as evidenced by numerous cases of accidental poisonings of human and animal populations and their extreme toxic potency in laboratory animals. The proposed model for the mechanism of action of TCDD and related compounds is analogous to that of the steroid hormones, which modulate gene expression through a receptor mechanism. In the steroid receptor model, the compound enters the cell cytoplasm where it acts as a specific ligand, binding selectively to a high affinity receptor protein. Bound to the appropriate ligand, the receptor concentrates in the nucleus where its increased association with chromatin leads to altered gene expression. This model has been useful in characterizing the Ah receptor; however, it does not provide a unifying hypothesis for all biochemical and toxic effects associated with exposure to halogenated aromatic hydrocarbons. Several findings suggest that a primary factor in determining TCDD toxicity might be tissue and species specific factors that control the actions of Ah receptor(s) in target tissues. Furthermore, numerous mechanisms might be involved. Clarifying the mechanism(s) for TCDD toxicity would enhance our ability to predict human health consequences to toxic halogenated aromatic hydrocarbons and would provide a more rational basis for risk analysis.